Control of programmed cell death by the baculovirus genes p35 and iap. - Clem, R J (1994)
The SF-21 insect cell line undergoes rapid and widespread apoptosis when treated with actinomycin D or when infected with a mutant of the baculovirus Autographa californica nuclear polyhedrosis virus lacking a p35 gene or a functionally active iap (inhibitor of apoptosis) gene. Here we provide evidence that the basis for the induction of apoptosis by these two different stimuli is the cessation of RNA synthesis. We also show that expression of either p35 or two different functional iap homologs blocks apoptosis independently of other viral genes, indicating that these gene products act directly on the cellular apoptotic pathway. The iap genes encode a C3HC4 (or RING) finger motif found in a number of transcriptional regulatory proteins, as well as two additional Cys/His motifs (baculovirus iap repeats). We show that specific amino acids within both the C3HC4 finger and the N-terminal baculovirus iap repeat are critical for anti-apoptosis function. Overexpression of either mammalian bcl-2 or adenovirus E1B-19K, genes which block apoptosis when overexpressed in a number of mammalian cells, does not block actinomycin D-induced apoptosis in SF-21 cells.